2022
DOI: 10.2105/ajph.2022.306879
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Massachusetts’ Statewide Sales Restriction on Flavored and Menthol Tobacco Products on Tobacco Sales in Massachusetts and Surrounding States, June 2020

Abstract: In June 2020, Massachusetts implemented a first in the nation statewide law that restricts sales of menthol and other flavored tobacco. Since implementation, sales data indicate high retailer compliance. Drastic decreases were seen in sales of all flavored tobacco. Most neighboring states did not see increases in overall tobacco sales, although New Hampshire saw an initial increase in menthol sales, which was not sustained. We found that menthol restrictions are effective and that federal-level legislation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…These study findings are consistent with a recent study demonstrating high retailer compliance and large decreases in the sales of all flavored tobacco following policy implementation in Massachusetts 30 . Similarly, a study of the statewide flavor policy in New York found that while there were decreases in past 30-day e-cigarette use, cigarette, and dual use of e-cigarettes and cigarettes, were observed over the 2-year period in New York State post implementation; 95% of vapers still reported using a non-tobacco-flavored e-cigarette following the restriction 31 .…”
Section: Discussionsupporting
confidence: 92%
“…These study findings are consistent with a recent study demonstrating high retailer compliance and large decreases in the sales of all flavored tobacco following policy implementation in Massachusetts 30 . Similarly, a study of the statewide flavor policy in New York found that while there were decreases in past 30-day e-cigarette use, cigarette, and dual use of e-cigarettes and cigarettes, were observed over the 2-year period in New York State post implementation; 95% of vapers still reported using a non-tobacco-flavored e-cigarette following the restriction 31 .…”
Section: Discussionsupporting
confidence: 92%
“…Prior reports have found conflicting results related to changes in cigarette sales in border states following the Massachusetts law [ 3 , 4 ]. However, these reports did not assess the statistical significance of sales trends or account for potential confounding factors, such as e-cigarette flavor polices, the COVID-19 pandemic, and differences across states in sociodemographic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a Massachusetts government report found cigarette tax revenue declined statewide during 2021–2022; the same report also found cigarette tax revenue increased in some neighboring states [ 3 ]. In contrast, a recent study has shown that overall tobacco sales decreased in most neighboring states following the Massachusetts law [ 4 ]. The impact of the Massachusetts law on cigarette sales in bordering states, controlling for potential confounding factors, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The net decline in total cigarette sales after the Massachusetts comprehensive menthol flavor ban was consistent with a previously published study’s findings and demonstrates that initial increases in cigarette sales in the bordering states were not sustained . Limitations of this study are that online cigarette sales were not accounted for and that Massachusetts implemented other tobacco control policies that could affect the results.…”
Section: Discussionmentioning
confidence: 99%
“…
2/3 in cigarette sales in the bordering states were not sustained. 4 Limitations of this study are that online cigarette sales were not accounted for and that Massachusetts implemented other tobacco control policies that could affect the results. The findings demonstrate that the US Food and Drug Administration's ban on menthol cigarettes may reduce overall cigarette consumption nationwide.
…”
mentioning
confidence: 99%